Corpus Linguistics of the Uzbek Language and its Possibilities (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the study of the Uzbek language within the framework of corpus linguistics, focusing on existing electronic corpora, their structure, and their potential for both academic and practical applications. Particular emphasis is placed on the automatic analysis of lexical, grammatical, stylistic, and pragmatic features of the Uzbek language using corpus tools. The paper also discusses the role of corpus linguistics in language teaching, translation, and linguistic research.